Written Practices na Maia: A Newly Discovered Source of Old Hispanic Notation from Portugal - Elsa De Luca; Ainoa Castro Correa (Studia Historica. Historia Medieval)
This study introduces a manuscript kept in the Arquivo da Torre do Tombo which represents the third source with Old Hispanic notation found in Portuguese territories, and the first recovered from a charter. This unique document is significant given the paucity of extant sources with this type of notation, and because few are securely dated whilst this one allows for a better chronological contextualisation. Likewise, this source is relevant because it is linked to a context of rural and mostly secular written production in a period of change towards monastic rule. Focusing on this peculiar charter, in the following pages we will introduce the most significant aspects of its materiality, shedding light on the world of scribes operating in northern Portugal and opening up new possibilities for a better understanding of the patchy scenario of diffusion and use of Old Hispanic notation.